Determinants of breast cancer in Saudi women from Makkah region: a case-control study (breast cancer risk factors among Saudi women) - Fatmah J. Alsolami; Firas S. Azzeh; Khloud J. Ghafouri; Mazen M. Ghaith; Riyad A. Almaimani; Hussain A. Almasmoum; Rwaa H. Abdulal; Wesam H. Abdulaal; Abdelelah S. Jazar; Sufyan H. Tashtoush (BMC, 2019)
Abstract Background There are various factors that play a major role in influencing the overall health conditions of women diagnosed with breast cancer. The population of women in Makkah region are diverse, therefore it is significant to highlight the possible determinants of breast cancer in this population. This is a case-control study that assessed determinants of breast cancer including socioeconomic factors, health-related characteristics, menstrual histories and breastfeeding among postmenopausal women in Makkah region in Saudi Arabia. Methods A total of 432 female participants (214 cases and 218 controls) were recruited for this study. A validated questionnaire was completed by trained dietitians at King Abdullah Medical City Hospital in the Makkah region of Saudi Arabia. Results Results displayed that determinants of breast cancer were associated significantly (P < 0.05) with unemployment, large family size, lack of knowledge and awareness about breast cancer, obesity, sedentary lifestyle, smoking, starting menarche at an early age, as well as hormonal and non-hormonal contraceptive use. There was no effect of diabetes, hypertension, hyperlipidemia, and duration of breastfeeding on the incidence of breast cancer. Conclusion In summary, the results of this study accentuate the possible effect of socioeconomic factors, health-related characteristics and menstrual history on the incidence of breast cancer in postmenopausal women in the Makkah region. Education programs should be applied to increase breast cancer awareness and possibly decrease its incidence.